2022
DOI: 10.3897/folmed.64.e64714
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial effect of Pimpinella anisum essential oil on Enterococcus faecalis, Lactobacillus casei, Actinomyces naeslundii, and Aggregatibacter actinomycetemcomitans

Abstract: Introduction: Pimpinella anisum is a medicinal plant with antimicrobial, antifungal, and anti-oxidative properties. Limited studies have assessed the antibacterial properties of Pimpinella anisum on oral and dental pathogens. Aim: This in vitro study aimed to assess the antibacterial effect of Pimpinella anisum essential oil on Enterococcus faecalis, Lactobacillus casei, Actinomyces naeslundii, and Aggregatibacter actinomycetemcomitans. Materials and methods: After obtaining the essential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The utmost use of anise seed in animals is as antibacterial, antifungal, insecticidal, muscle relaxant, analgesic, laxative and antioxidant (Ashry et al 2022;Bakhshi et al 2022). However, it has also been tested as growth promoter in fewer studies and has been found to improve FCR in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The utmost use of anise seed in animals is as antibacterial, antifungal, insecticidal, muscle relaxant, analgesic, laxative and antioxidant (Ashry et al 2022;Bakhshi et al 2022). However, it has also been tested as growth promoter in fewer studies and has been found to improve FCR in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Aniseed is used as a flavoring agent for bread, biscuits, cookies, sweets, and ice cream [25,26]. Aniseed essential oil possesses antioxidant [27,28], antimicrobial [29,30], anti-inflammatory [31], and hepatoprotective properties [32]. According to the European Medicine Agency (EMA) [33], aniseed is recommended for the treatment of a variety of symptoms of the digestive tract, such as dyspepsia, Helicobacter infections, and spasmodic gastro-intestinal complaints including bloating and flatulence, as well as respiratory tract discomforts including catarrh, and as an expectorant in cough and cold.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, numerous studies have explored the potential benefits of polyphenols in addressing reproductive disorders ( 18 , 19 ). Pimpinella anisum L. ( P. anisum ), commonly known as aniseed or anise, is an aromatic plant belonging to the Umbelliferae (Apiaceae) family, primarily found in the Middle East, Asia Minor, and India ( 20 , 21 ). Aniseed extract contains various compounds, including 1.5 - 6% essential oil (mainly trans-anethole), 8 - 11% fatty acids (such as palmitic and oleic acids), 4% carbohydrates, and 18% protein, along with significant amounts of phenolic compounds, such as flavonoids and phenolic acids ( 22 ).…”
Section: Introductionmentioning
confidence: 99%